2005
DOI: 10.1093/intqhc/mzi049
|View full text |Cite
|
Sign up to set email alerts
|

Quality of pharmacies in Pakistan: a cross-sectional survey

Abstract: Most drug sellers had fragmentary knowledge regarding drug dispensing and storage, and improper dispensing practices. There is a need to enforce existing legislation with training programmes directed towards drug sellers and to involve the pharmaceutical industry, which plays an important role in influencing pharmacy knowledge and practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
90
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 25 publications
10
90
2
1
Order By: Relevance
“…The demographic characteristics of the current study lends some support to this assertion. It is also buttressed by a previous study by Butt et al [16] in which there were only three female pharmacist respondents.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The demographic characteristics of the current study lends some support to this assertion. It is also buttressed by a previous study by Butt et al [16] in which there were only three female pharmacist respondents.…”
Section: Discussionmentioning
confidence: 85%
“…According to the report of the Health System Review Mission Pakistan [15], there are more than 8000 pharmacists in Pakistan but only 10% of them are engaged in community pharmacy practice. Similarly, a cross-sectional survey of the quality of pharmacies in Pakistan reported nominal presence of professionally qualified pharmacists [16]. This underutilization of professionally qualified pharmacists in community settings in Pakistan may be attributed to their perceived status as 'less respectable healthcare professional' in the eyes of the public when compared to pharmacists employed in hospital, industrial and academic settings [17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the miserable part of current scenario is the poor health information system, which does not produce the quality data required for planning. 13 …”
Section: Health Care Systemmentioning
confidence: 99%
“…The outlets are registered with the certificate of registration, but the quality of clinical and/ or pharmaceutical care has been reported to be poor. 3 We are lacking the major components of patient's pharmaceutical care i.e. prescribing, administering, documenting and reviewing the drug usage.…”
mentioning
confidence: 99%
“…[1] For developing country like Pakistan where widespread access to health care is a far-reaching cry, patients often resort to self-medication for most of their ailments, driven by lack of access to health care system, cultural and financial constraints. [2] Number of studies has reported that self-medication may cause un-due delay in seeking health care services leading to, at some instances, irreversible damage due to some life threatening drug interactions. [3] Corticosteroids are among highly abused drugs, freely available at local medical stores without prescription in developing countries like Pakistan.…”
Section: Introductionmentioning
confidence: 99%